ISLAM WASATIYAH - Ahmad Dimyati (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2017)
Islam wasathiyah is the optics from umat who are be a look at center the manner, righteous, harmonious principle in the middle umanity that dinamic and multiple diverse. Islam wasathiyah invited in each an individual had charge of other individual with solidarity who is build up in an organic manner. Middle rail becomed Islam wasthiyah as be medium to have serve purpose of Islam observe two side as balanced. Islam wasathiyah not be rid of root word identity “moderat” which is to provide humanist-dialogues values, give priority to strenght of confraternity better than dominance, justness above rightful authority, harmonious about tolerance interfaith and avoided behavior at the course that is extreme. From here, Islam wasathiyah position be offer to the umanity so as to avoid from long lasting conflict that fine above the name of ideology, humanism, and reach of legal ground politicization until at last madani of life will be build up in particular of south east asia region.